Effect of varied processing conditions on the capsaicin value of powdered siling labuyo (Capsicum frutescens Linn. Fruw.) - Moises, Benilda D.; Rillo, Belen O. (1986.)
The study was aimed at determining favorable conditions for minimizing loss of pungency in "siling labuyo" powder during processing. In Phase I, the effect of varied drying temperatures on the capsaicin value of powdered "siling labuyo" was determined. Three drying temperatures were tested: 120°F, 150°F and 175°F. Results of subjective tests conducted showed that pods dried at 150°F has the highest Scoville Value and lowest was obtained from pods dried at 175°F. In Phase II, the effect of varied mesh sieve sizes used for grinding on the capsaicin value of powderes "siling labuyo" was determined. The pods dried at 150°F were passed through a pulverizer at different mesh sizes: 36, 64 and 80. The highest Scovilole value was obtained from pods ground at mesh 80, second at mesh 64 and lowest at mesh 36. However, triangle tests conducted showed that there are no significant differences in pungency of the powder samples. In Phase III, the effect of varied pretreatments before drying and grinding was determined. Grinding without seeds resulted in a lower percentage yield compared to grinding with seeds but the very high final Scoville value of "siling labuyo" ground without the seeds compensates for the low yield. Cutting the pods into halves before drying proved economical with 2 hours and 35 minutes lesser drying time required to reach the final 4.0% moisture endpoint compared to drying the pods in whole form.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peppers